Phosphate adsorbent as well as preparation method and application thereof
By reacting bentonite with trivalent iron solution to prepare clay-iron complex, the existing phosphate adsorbents have been solved, the problems of high cost, pollution and insufficient adsorption capacity have been achieved, and the efficient phosphate adsorption effect has been achieved, and iron oxides have been reduced. the pollution effect.
Patent Information
- Application Number
- CN202411316551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing phosphate adsorbents are costly when removing phosphate in water bodies, which may cause pollution or insufficient adsorption capacity. Commonly used materials such as activated carbon are expensive, iron oxides entering water bodies may cause pollution, and clay minerals have weak adsorption capacity.
By reacting bentonite with trivalent iron solution, an iron-loaded bentonite solution is formed, and the pH is adjusted and freeze-dried, a clay-iron complex with a high specific surface area is prepared as a phosphate adsorption agent, which improves its adsorption ability to phosphate. and reduce the impact of iron oxides.
The prepared clay-iron composite has great phosphate adsorption capacity, with an adsorption rate of 88.165%, which is higher than that of traditional clay and clay-goite mixtures. At the same time, the iron content in the composite is reduced and it has a higher environmental protection. value.
Smart Images

Figure CN119186484A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbents, and in particular to a phosphate adsorbent and a preparation method and application thereof. Background Art
[0002] Phosphorus is a key factor in the eutrophication of water bodies. In severe cases, it may cause environmental pollution and ecological damage. In recent years, driven by the country's implementation of ecological civilization construction, the control of phosphorus eutrophication in water environments has gradually tended to use means that have no impact on the ecological environment. At present, common phosphorus removal technologies are mainly divided into three categories: physical, chemical and biological phosphorus removal. For water environment management, chemical precipitation phosphorus removal costs are high and easily cause secondary pollution. Biological phosphorus removal takes a long time and is affected by factors such as water quality, temperature, and pH. It cannot be widely applied to a variety of waters. Based on this, physical remediation is currently the main measure for the control of phosphorus pollution in water bodies. Among them, the adsorption method is regarded as the most commonly used phosphate removal technology because of its simple principle, easy operation, and obvious effect.
[0003] At present, the commonly used adsorption methods mainly improve the adsorption capacity of phosphates by synthesizing new materials or improving the physical and chemical properties of common adsorption materials. Activated carbon, metal oxides, clay minerals, etc. are widely selected adsorbents on the market, each with its own advantages and disadvantages. For example, activated carbon has extremely strong adsorption capacity but is extremely expensive; metal oxides, especially iron oxides, also have strong phosphorus adsorption capacity and are more cost-effective than activated carbon, but entering the water may cause iron pollution and other effects; clay mineral iron oxides have price advantages and harmless properties compared to activated carbon, but their adsorption capacity is slightly weaker.
[0004] Based on the defects of current phosphorus adsorbents, it is necessary to improve them. Summary of the invention
[0005] In view of this, the present invention aims at the deficiencies of the prior art and proposes a phosphate adsorbent and a preparation method and application thereof, so as to solve or at least partially solve the defects of the prior art.
[0006] The present invention is achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a phosphate adsorbent, comprising the following steps:
[0008] Adding bentonite to the ferric iron solution and shaking to obtain an iron-loaded bentonite solution;
[0009] After centrifuging the iron-loaded bentonite solution, the supernatant was discarded to obtain a first precipitate;
[0010] adding water to the first precipitate, adjusting the pH to neutral, and shaking to obtain a complex solution;
[0011] After centrifuging the complex solution, the supernatant was discarded to obtain a second precipitate;
[0012] The second precipitate is frozen and then dried to obtain a clay-iron complex, which is a phosphate adsorbent.
[0013] Preferably, the ferric iron solution includes at least one of a FeCl3 solution, a Fe(NO3)3 solution, and a Fe2(SO4)3 solution.
[0014] Preferably, bentonite is added to the ferric iron solution and shaken in a shaker at a rotation speed of 200 to 250 rpm and a temperature of 20 to 30° C. for 20 to 30 hours to obtain an iron-loaded bentonite solution.
[0015] Preferably, the iron-loaded bentonite solution is centrifuged at 3000-5000 rpm and 20-30° C. for 5-20 min, the supernatant is discarded, and the solution is washed to obtain a first precipitate.
[0016] Preferably, water is added to the first precipitate, ultrasonically dispersed for 5 to 15 minutes, the pH is adjusted to neutral using a NaOH solution, and shaken in a shaker at a speed of 200 to 250 rpm and a temperature of 20 to 30° C. for 20 to 30 hours to obtain a complex solution.
[0017] Preferably, the complex solution is centrifuged at 3000-5000 rpm and 20-30° C. for 5-20 min, the supernatant is discarded, and the solution is washed to obtain a second precipitate.
[0018] Preferably, in the step of freezing the second precipitate, the freezing temperature is -20 to -25°C and the freezing time is 20 to 30 hours.
[0019] Preferably, the concentration of the ferric iron solution is 0.05 to 0.2 M;
[0020] The mass volume ratio of the bentonite to the ferric iron solution is (3-7) g:(1-2) L.
[0021] In a second aspect, the present invention further provides a phosphate adsorbent prepared by the preparation method.
[0022] In a third aspect, the present invention also provides a use of the phosphate adsorbent in removing phosphate from water.
[0023] The preparation method of the phosphate adsorbent of the present invention has the following beneficial effects compared with the prior art:
[0024] The preparation method of the phosphate adsorbent of the present invention greatly improves the adsorption capacity of the clay mineral by combining iron oxide and clay mineral (i.e. bentonite); the specific surface area of the phosphate adsorbent clay-iron complex prepared by the present invention is 87.6 m 2 / g, higher than 63.6m / g of clay 2 / g, the adsorbent prepared by the present invention has a large specific surface area; experiments show that the clay-iron complex prepared by the present invention has a maximum adsorption capacity of 1.936 mg / g for phosphate, and an adsorption rate of 88.165%; while the maximum adsorption capacity of clay for phosphate is 0.054 mg / g, and the adsorption rate is 4.314%, and the maximum adsorption capacity of clay-goethite mixture for phosphate is 0.668±0.036 mg / g, and the adsorption rate is 86.482%. Compared with clay and clay-goethite mixture, the clay-iron complex prepared by the present invention has a great adsorption capacity for phosphate; at the same time, the present invention combines iron oxide and clay mineral (i.e. bentonite) to reduce the influence of iron oxide while improving the adsorption capacity of clay mineral. Compared with previous similar combining methods, the bentonite selected in the present invention has a stronger phosphorus adsorption capacity and an expanded structure that is conducive to the loading of iron; and after the iron is combined with the bentonite, the iron ion solution and the complex are separated and then the iron oxide is synthesized. Compared with the previous method of directly mixing iron oxide and clay minerals or synthesizing iron oxide in a state where clay minerals are dispersed in an iron ion solution, the phosphorus adsorption capacity increased by the iron oxide is retained while the iron content in the complex is reduced, which has a higher environmental value. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 The clay-iron complex prepared in Example 1 and the X-ray diffraction pattern of the clay;
[0027] Figure 2 The clay-iron complex prepared in Example 1 and the Zeta potential change diagram of the clay at pH 2 to 8;
[0028] Figure 3 This is an atomic force microscope image of the clay-iron complex prepared in Example 1.
[0029] Figure 4 The transmission electron microscope image and EDS spectrum image of the clay-iron complex prepared in Example 1;
[0030] Figure 5 : are nitrogen adsorption-desorption curves of the clay-iron complex and clay prepared in Example 1;
[0031] Figure 6 is the Mössbauer spectrum of the clay-iron composite prepared in Example 1;
[0032] Figure 7 is the phosphorus adsorption capacity of clay-iron complex under different phosphorus concentrations;
[0033] Figure 8 isothermal adsorption curve and adsorption kinetic curve of phosphate by the clay-iron complex prepared in Example 1;
[0034] Fig. 9 is the phosphorus adsorption capacity of clay at different phosphorus concentrations in Comparative Example 1;
[0035] Fig.10 This is the adsorption capacity of phosphorus by the clay-goethite mixture at different phosphorus concentrations in Comparative Example 2. DETAILED DESCRIPTION
[0036] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.
[0039] The present invention provides a method for preparing a phosphate adsorbent, comprising the following steps:
[0040] S1, adding bentonite to the ferric iron solution, shaking, to obtain an iron-loaded bentonite solution;
[0041] S2, centrifuging the iron-loaded bentonite solution, discarding the supernatant, and obtaining a first precipitate;
[0042] S3, adding water to the first precipitate, adjusting the pH to neutral, and shaking to obtain a complex solution;
[0043] S4, centrifuging the complex solution, discarding the supernatant, and obtaining a second precipitate;
[0044] S5. Freeze the second precipitate and then dry it to obtain a clay-iron complex, which is a phosphate adsorbent.
[0045] The present invention selects to combine iron oxide and clay mineral (i.e. bentonite) to greatly improve the adsorption capacity of clay mineral; the specific surface area of the phosphate adsorbent clay-iron complex prepared by the present invention is 87.6m 2 / g, higher than 63.6m / g of clay 2 / g, the adsorbent prepared by the present invention has a large specific surface area; experiments show that the clay-iron complex prepared by the present invention has a maximum adsorption capacity of 1.936 mg / g for phosphate, and an adsorption rate of 88.165%; while the maximum adsorption capacity of clay for phosphate is 0.054 mg / g, and the adsorption rate is 4.314%, and the maximum adsorption capacity of clay-goethite mixture for phosphate is 0.668±0.036 mg / g, and the adsorption rate is 86.482%. Compared with clay and clay-goethite mixture, the clay-iron complex prepared by the present invention has a great adsorption capacity for phosphate; at the same time, the present invention combines iron oxide and clay mineral (i.e. bentonite) to reduce the influence of iron oxide while improving the adsorption capacity of clay mineral. Compared with previous similar combining methods, the bentonite selected in the present invention has a strong phosphorus adsorption capacity and an expanded structure that is conducive to the loading of iron; and after the iron is combined with the bentonite, the iron ion solution and the complex are separated and then the iron oxide is synthesized. Compared with the previous method of directly mixing the iron oxide and the clay mineral or synthesizing the iron oxide in the state where the clay mineral is dispersed in the iron ion solution, the phosphorus adsorption capacity increased by the iron oxide is retained while the iron content in the complex is reduced (the iron content in the clay-iron complex prepared in Example 1 of the present invention accounts for about 5%, while the iron content of the previous mixture of iron oxide and clay mineral accounts for about 20%. The present invention has a very high phosphorus adsorption capacity while reducing the iron content in the complex), and has a higher environmental value.
[0046] In some embodiments, the ferric iron solution includes at least one of a FeCl3 solution, a Fe(NO3)3 solution, and a Fe2(SO4)3 solution.
[0047] In some embodiments, bentonite is added to a ferric iron solution and shaken in a shaker at a speed of 200-250 rpm and a temperature of 20-30° C. for 20-30 h to obtain an iron-loaded bentonite solution.
[0048] In some embodiments, the iron-loaded bentonite solution is centrifuged at 3000-5000 rpm and 20-30° C. for 5-20 min, the supernatant is discarded, and the solution is washed to obtain a first precipitate.
[0049] In some embodiments, water is added to the first precipitate, ultrasonically dispersed for 5 to 15 minutes, the pH is adjusted to neutral using a NaOH solution, and the mixture is shaken in a shaker at a speed of 200 to 250 rpm and a temperature of 20 to 30° C. for 20 to 30 hours to obtain a complex solution.
[0050] Specifically, in the above embodiment, the concentration of NaOH solution is 0.5-1M.
[0051] In some embodiments, the complex solution is centrifuged at 3000-5000 rpm and 20-30° C. for 5-20 min, the supernatant is discarded, and the solution is washed to obtain a second precipitate.
[0052] In some embodiments, in the step of freezing the second precipitate, the freezing temperature is -20 to -25°C, and the freezing time is 20 to 30 hours.
[0053] In some embodiments, the concentration of the ferric iron solution is 0.05 to 0.2 M;
[0054] In some embodiments, the mass volume ratio of bentonite to ferric iron solution is (3-7) g: (1-2) L.
[0055] In some embodiments, the second precipitate is frozen, dried, ground with a mortar, and passed through a 50-150 mesh sieve to obtain a clay-iron complex, which is a phosphate adsorbent.
[0056] Based on the same inventive concept, the present invention also provides a phosphate adsorbent, which is prepared by the above-mentioned preparation method.
[0057] Based on the same inventive concept, the present invention also provides the use of the above-mentioned phosphate adsorbent in removing phosphate from water.
[0058] The following further illustrates the phosphate adsorbent of the present application and its preparation method and application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0059] Example 1
[0060] The present invention provides a method for preparing a phosphate adsorbent, comprising the following steps:
[0061] S1, add 5g bentonite to 1L 0.1M FeCl3 solution, shake in a shaker at 220rpm and 25℃ for 24h to obtain an iron-loaded bentonite solution;
[0062] S2, centrifuging the iron-loaded bentonite solution at 3000 rpm and 25° C. for 10 min, discarding the supernatant, and washing three times with ultrapure water to obtain a first precipitate;
[0063] S3, add 1L of water to the first precipitate, ultrasonically disperse for 10 minutes, adjust the pH to 7 with 0.5M NaOH solution, and shake in a shaker at a speed of 220 rpm and a temperature of 25°C for 24 hours to obtain a complex solution;
[0064] S4, centrifuging the complex solution at 3000 rpm and 25°C for 10 min, discarding the supernatant, and washing three times with ultrapure water to obtain a second precipitate;
[0065] S5. Freeze the second precipitate at -20°C for 24 hours, dry it, grind it with a mortar, and pass it through a 100-mesh sieve to obtain a clay-iron complex, which is a phosphate adsorbent.
[0066] Example 2
[0067] This embodiment provides an application of a phosphate adsorbent in removing phosphate from water, comprising the following steps:
[0068] 0.04 g of the clay-iron complex prepared in Example 1 was added to 20 mL of a solution with a phosphorus concentration of 1 mg / L, 2 mg / L, 3 mg / L, 4 mg / L, and 5 mg / L (specifically, a KH2PO4 solution), and the residual phosphorus content was measured by centrifugation after oscillation at 220 rpm for 24 h, and the adsorption capacity of the clay-iron complex for phosphorus was calculated.
[0069] Comparative Example 1
[0070] This comparative example provides an application of a phosphate adsorbent in removing phosphate from water, comprising the following steps:
[0071] S1. Add 0.04 g of clay (i.e., the bentonite used in Example 1) to 20 mL of a solution with a phosphorus concentration of 1 mg / L, 2 mg / L, 3 mg / L, 4 mg / L, and 5 mg / L (specifically, a KH2PO4 solution), shake at 220 rpm for 24 h, and then centrifuge to measure the residual phosphorus content, and calculate the adsorption capacity of the clay for phosphorus.
[0072] Comparative Example 2
[0073] This comparative example provides a method for preparing a phosphate adsorbent, comprising the following steps:
[0074] S1, mixing clay (i.e., bentonite used in Example 1) and goethite in a mass ratio of 1:1 to obtain a clay-goethite mixture;
[0075] The synthesis method of goethite is as follows: weigh 27.03 g of ferric chloride hexahydrate and add 1 L of water to prepare a 0.1 M FeCl3 solution, add 0.1 M KOH to adjust the pH to 7, transfer to a reactor and age at 70° C. for 48 h, centrifuge at 5000 rpm for 10 min, rinse with water, centrifuge at 5000 rpm for 10 min again, repeat three times, collect the precipitate, freeze-dry it, and store it at -20° C. for future use;
[0076] S2. Add 0.04 g of the clay-goethite mixture in step S1 to 20 mL of a solution with a phosphorus concentration of 1 mg / L, 2 mg / L, 3 mg / L, 4 mg / L, and 5 mg / L (specifically, a KH2PO4 solution), shake at 220 rpm for 24 hours, and then centrifuge to measure the remaining phosphorus content, and calculate the adsorption capacity of the clay-ferrihydrite mixture for phosphorus.
[0077] Performance Characterization
[0078] Figure 1 The X-ray diffraction patterns of the clay-iron complex prepared in Example 1 and the clay (ie, the bentonite used in Example 1) are shown.
[0079] from Figure 1 It can be seen that the structure of the clay 001 crystal surface was changed after iron loading.
[0080] Figure 2 Graph showing the Zeta potential change from pH 2 to 8 of the clay-iron complex prepared in Example 1 and the clay (ie, the bentonite used in Example 1).
[0081] from Figure 2 It can be seen that as the environmental pH decreases, the material potential gradually increases, and the potential of the clay-iron complex is higher than that of the clay, indicating that iron loading in the clay changes the electrical properties of the clay.
[0082] Figure 3 This is an atomic force microscope image of the clay-iron complex prepared in Example 1. Figure 3 A, B, and C represent atomic force microscopy images at different magnifications.
[0083] from Figure 3 It can be seen that the clay-iron complex prepared in Example 1 exhibits a tightly compounded cluster morphology.
[0084] Figure 4 The transmission electron microscope image and EDS energy spectrum image of the clay-iron complex prepared in Example 1 are shown. Figure 4 A is a transmission electron microscope image, B is an enlarged image of the box in Figure A, and C is an EDS energy spectrum image.
[0085] from Figure 4 It can be seen that particles similar to amorphous iron oxides were found on the surface of the clay, and elemental analysis showed that the distribution of iron and silicon was extremely similar, indicating that the clay and iron were tightly combined in space.
[0086] Figure 5 ] are nitrogen adsorption and desorption curves of the clay-iron complex prepared in Example 1 and the clay (ie, the bentonite used in Example 1).
[0087] The specific surface areas of the clay-iron composite prepared in Example 1 and the clay (i.e., bentonite used in Example 1) are shown in Table 1 below.
[0088]
[0089]
[0090] It can be seen from Table 1 that the specific surface area of the clay-iron composite prepared by the present invention is 87.6 m 2 / g, higher than 63.6m / g of clay 2 / g.
[0091] Figure 6 This is the Mössbauer spectrum of the clay-iron composite prepared in Example 1.
[0092] from Figure 6 It can be seen that the main form of iron in the clay-iron composite prepared in Example 1 is ferrihydrite.
[0093] According to the method in Example 2, the adsorption capacity of phosphorus by the clay-iron complex at different phosphorus concentrations was calculated. The results are as follows: Figure 7 shown.
[0094] from Figure 7 It can be seen that the clay-iron complex prepared in Example 1 has the highest phosphate adsorption capacity of 1.936 mg / g, and the adsorption rate is 88.165%.
[0095] Figure 8 The isothermal adsorption curve and adsorption kinetic curve of the clay-iron complex prepared in Example 1 for phosphate are shown; specifically, 0.01 g of the clay-iron complex prepared in Example 1 was added to 20 mL of a solution with a phosphorus concentration of 0.5 mg / L, 1 mg / L, 2 mg / L, 3 mg / L, 5 mg / L, 10 mg / L, 20 mg / L, and 30 mg / L (specifically a KH2PO4 solution), and the residual phosphorus content was measured by centrifugation after oscillation at 220 rpm for 24 h, the adsorption capacity of the clay-iron complex for phosphorus was calculated, and the Langmuir and Freundlich models were used to fit the isothermal adsorption curve; 0.01 g of the clay-iron complex was added to 20 mL of a solution with a phosphorus concentration of 10 mg / L, and the residual phosphorus content was measured by centrifugation after oscillation at 220 rpm for 24 h, the phosphorus adsorption capacity of the complex was calculated, and the adsorption kinetic curve was fitted using pseudo-first-order kinetics and pseudo-second-order kinetics models.
[0096] The fitting parameters of the isothermal adsorption curve of phosphate by the clay-iron complex prepared in Example 1 are shown in Table 2 below. max The maximum adsorption capacity of phosphate by the complex is fitted by the Langmuir model, kL and k F are the adsorption rates fitted by the Langmuir and Freundlich models, respectively. n is the affinity of the adsorbent to the adsorbate fitted by the Freundlich model. Generally, when the value of 1 / n is between 0.1 and 0.5, it is believed that the adsorption reaction is easy to occur. Freundlich has a higher R 2 , indicating that the adsorption of phosphate by clay-iron complex is more inclined to irregular multilayer adsorption, and it has a stronger adsorption effect and more stable binding ability for phosphate.
[0097] Table 2 - Isotherm adsorption curve fitting parameters of clay-iron complex for phosphate
[0098]
[0099] The fitting parameters of the adsorption kinetic curve of phosphate by the clay-iron complex prepared in Example 1 are shown in Table 3 below. Q1 and Q2 are the maximum adsorption amount of phosphate by the complex fitted by the pseudo-first-order kinetic model and the pseudo-second-order kinetic model, respectively. K1 and K2 are the adsorption rates fitted by the pseudo-first-order kinetic model and the pseudo-second-order kinetic model, respectively. The pseudo-second-order kinetic model has a higher R 2 , indicating that the adsorption of phosphate by clay-iron complex is more inclined to irregular multilayer adsorption, and it has a stronger adsorption effect and more stable binding ability for phosphate.
[0100] Table 3 - Fitting parameters of the kinetic curve of phosphate adsorption by clay-iron complex
[0101]
[0102] According to the method in Comparative Example 1, the adsorption capacity of clay for phosphorus at different phosphorus concentrations was calculated. The results are as follows: Fig. 9 shown.
[0103] from Fig. 9 It can be seen that the clay in Comparative Example 1 has the highest phosphate adsorption capacity of 0.054 mg / g, and the adsorption rate is 4.314%.
[0104] According to the method in Comparative Example 2, the adsorption capacity of clay-goethite mixture for phosphorus at different phosphorus concentrations was calculated. The results are as follows: Fig.10 shown.
[0105] from Fig.10 It can be seen that the clay-goethite mixture in Comparative Example 2 has the highest phosphate adsorption capacity of 0.668±0.036 mg / g, and the adsorption rate is 86.482%.
[0106] According to the methods in Example 2 and Comparative Examples 1-2, the adsorption capacity of phosphorus by different adsorbents at different phosphorus concentrations was calculated. The results are shown in Table 4 below.
[0107] Table 4 - Phosphorus adsorption capacity of different adsorbents
[0108]
[0109] It can be seen from Table 4 that as the phosphate concentration increases, the amount of phosphorus adsorbed will increase and the adsorption rate will decrease. Therefore, the strongest adsorption capacity of the clay-iron complex of the present invention is when the initial concentration is 5 mg / L, and the maximum adsorption rate is when the initial concentration is 1 mg / L (test concentration); and the clay-iron complex of the present invention has a much higher phosphorus adsorption capacity than clay and clay-goethite mixture.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a phosphate adsorbent, characterized in that: The following steps are involved: Adding bentonite to the trivalent iron solution and shaking to obtain an iron-loaded bentonite solution; After centrifuging the iron-loaded bentonite solution, the supernatant is discarded to obtain a first precipitate; adding water to the first precipitate, adjusting the pH to neutral, and shaking to obtain a complex solution; After centrifuging the complex solution, the supernatant was discarded to obtain a second precipitate; The second precipitate is frozen and then dried to obtain a clay-iron complex, which is a phosphate adsorbent.
2. The method for preparing a phosphate adsorbent according to claim 1, characterized in that: The trivalent iron solution includes at least one of a FeCl3 solution, a Fe(NO3)3 solution, and a Fe2(SO4)3 solution.
3. The method for preparing a phosphate adsorbent according to claim 1, characterized in that: Bentonite is added to the trivalent iron solution, and shaken in a shaker at a rotation speed of 200-250 rpm and a temperature of 20-30° C. for 20-30 hours to obtain an iron-loaded bentonite solution.
4. The method for preparing a phosphate adsorbent according to claim 1, characterized in that: The iron-loaded bentonite solution is centrifuged at 3000-5000 rpm and 20-30° C. for 5-20 min, the supernatant is discarded, and the solution is washed to obtain a first precipitate.
5. The method for preparing a phosphate adsorbent according to claim 1, characterized in that: Add water to the first precipitate, perform ultrasonic dispersion for 5 to 15 minutes, adjust the pH to neutral using a NaOH solution, and shake in a shaker at a speed of 200 to 250 rpm and a temperature of 20 to 30° C. for 20 to 30 hours to obtain a complex solution.
6. The method for preparing a phosphate adsorbent according to claim 1, characterized in that: The complex solution is centrifuged at 3000-5000 rpm and 20-30° C. for 5-20 min, the supernatant is discarded, and the mixture is washed to obtain a second precipitate.
7. The method for preparing a phosphate adsorbent according to claim 1, characterized in that: In the step of freezing the second precipitate, the freezing temperature is -20 to -25°C and the freezing time is 20 to 30 hours.
8. The method for preparing a phosphate adsorbent according to claim 1, characterized in that: The concentration of the ferric iron solution is 0.05-0.2M; The mass volume ratio of the bentonite to the ferric iron solution is (3-7) g:(1-2) L.
9. A phosphate adsorbent, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the phosphate adsorbent as claimed in claim 9 in removing phosphate from water.
Citation Information
Patent Citations
Chelate exchanger
CN1882387A